Mapping Users’ Experience of a Family History and Genetic Risk Algorithm Tool in Primary Care - Miroševič, Špela; Krajc, Kaja; Klemenc-Ketiš, Zalika; Selič-Zupančič, Polona (Public health genomics, 2021)
Introduction: The development of a family history (FH) questionnaire (FHQ) provides an insight into a patient’s familiarity of a trait and helps to identify individuals at increased risk of disease. A critical aspect of developing a new tool is exploring users’ experience. Objective: The objective of this study was to examine users’ experience, obstacles and challenges, and their views and concerns in the applicability of a new tool for determining genetic risk in Slovenia’s primary care. Methods: We used a qualitative approach. The participants completed a risk assessment software questionnaire that calculates users’ likelihood of developing familial diseases. Audio-taped semi-structured telephone interviews were conducted to evaluate their experience. There were 21 participants, and analyses using the constant comparative method were employed. Results: We identified 3 main themes: obstacles/key issues, suggestions for improvements, and coping. The participants were poorly satisfied with the clarity of instructions, technical usability problems, and issues with the entry of relatives’ data. They expressed satisfaction with some of the characteristics of the FHQ (e.g., straightforward and friendly format, easy entry, and comprehension). They suggested simpler language, that the disease risk should be targeted toward the disease, that the FHQ should include patient-specific recommendations, and that it should be part of the electronic medical records. When discussing what would they do with the results of the FHQ, the participants used different coping strategies: active (e.g., seeking information) or passive (e.g., avoidance). Discussion/Conclusion: User experience was shown to be a synthesis of obstacles, overcoming them with suggestions for improvements, and exploration of various coping mechanisms that may emerge from dealing with the stressor of “being at risk.”